1991
DOI: 10.1080/00288233.1991.10417681
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early spring grazing frequency on the reproductive growth and development of a perennial ryegrass tiller population

Abstract: A population (1188) of vegetative perennial ryegrass tillers was identified at random in nine paddocks of an existing farmlet experiment. Groups of three paddocks (396 of identified tillers) were grazed every 8, 16, and 32 days from mid August until early November 1984, after which all paddocks were grazed every 32 days until the end of the experiment in May 1985. The physiologicalstatus (vegetative or reproductive) oflive marked tillers and their orientation in the sward were determined at 7-12-day intervals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 13 publications
1
9
1
Order By: Relevance
“…Herbage mass pre‐grazing followed a similar pattern to that of sward height, with treatment AR having lower values than treatment NR in June, and similar values for the remainder of the study. This is in agreement with Thom (1991) who reported that a short spring rotation (minimum 8 d) resulted in lower pre‐grazing herbage masses. Herbage allowance was determined above 4 cm, in accord with previous studies (Meijs and Hoekstra, 1984; Meijs, 1986).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Herbage mass pre‐grazing followed a similar pattern to that of sward height, with treatment AR having lower values than treatment NR in June, and similar values for the remainder of the study. This is in agreement with Thom (1991) who reported that a short spring rotation (minimum 8 d) resulted in lower pre‐grazing herbage masses. Herbage allowance was determined above 4 cm, in accord with previous studies (Meijs and Hoekstra, 1984; Meijs, 1986).…”
Section: Discussionsupporting
confidence: 93%
“…The impact on the grass plant of combining long and short rotations during the spring and summer has been investigated in New Zealand (Thom, 1991; Thom and Bryant, 1993; Hernandez Garay et al. , 1997), with short rotations shown to have positive effects on tiller density (Thom, 1991; Thom and Bryant, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Hamilton, New Zealand (37°47'S), the proportion of reproductive tillers for 'Ellett' was c. 25% in spring (November) of the second year (Table 1). Thom (1991) recorded a slightly lower figure of 18% in a mixed ('Grasslands Nui' and 'Ellett') perennial ryegrass and white clover pasture under dairy cow grazing, at the same research station. However, at a lower latitude (30°24'S) in Natal, South Africa, McKenzie (1997) reported that 'Ellett' tillers were mostly vegetative during spring (<9% reproductive) under subtropical conditions.…”
Section: Effects Of Nitrogen Fertiliser and Irrigation On Reproductivmentioning
confidence: 99%